Nieskończona Sprężysta Belka Timoshenki Uderzona Poprzecznie Skończonym Prętem Sprężystym - Kowalski, S.J. (Engineering Transactions, 1973)
The author calculates the duration of impact, contact forces and the mechanical energy trans- mitted from the rod to the beam; analysis of free vibrations of the beam after the rod is rebounded is also presented. It is shown that the increase of bending rate, bending moment and shear forces during the first phase of impact is greater in the case of rods of larger densities and Young moduli. the second phase of motion, however, the beam velocity and shearing forces decrease less rapidly, and the bending moments exhibit Jarger amplitudes in the case of rods of smaller densities and Young moduli (their mass being kept constant).